Extent and progression of atherosclerosis in carotid and subclavian arteries: the Carotid Artery Subclavian Artery study. Issue 8 (August 2021) - Pescetelli, Irene; Zimarino, Marco; Basso, Cristina; Ghirarduzzi, Angelo; Thiene, Gaetano; De Caterina, Raffaele
Abstract : Aims: To define the prevalence, progression, and the relationship between carotid and subclavian artery atherosclerosis and to identify factors associated with disease progression in a population of asymptomatic patients. Methods: Among all consecutive patients without a history of cardiovascular disease admitted to our hospital for duplex ultrasound examinations of the supra-aortic arteries, from January to December 2012, we retrospectively identified 530 patients with two evaluations at least 3 years apart. Each artery was graded according to stenosis degree, as absent or less than 20%, 20–49%, 50–69%, 70–99% and total occlusion. Disease progression was defined for any class increase at any time interval. Patients were grouped according to the presence of a more than 20% stenosis of the supra-aortic district at baseline, as controls, without atherosclerosis: n = 111, 21%; isolated carotid artery disease: n = 390, 74%; concomitant subclavian artery-carotid artery disease: n = 29, 5%. There were no cases with isolated subclavian artery atherosclerosis. Results: The mean time-lapse between the two evaluations was 3.1 ± 0.3 years; we documented disease progression in 32 patients (6%), all limited to the carotid artery ( P = 0.009 vs. controls, with no differences between isolated carotid artery disease and concomitant carotid and subclavian artery disease). Hypertension was significantly ( P < 0.001) associated with disease progression, regardless of the single or double district involvement. Conclusion: The subclavian artery is far less prone to atherosclerosis than the carotid artery, and features lesser disease progression. Understanding factors for the different susceptibility to atherosclerosis in these two close arterial districts provides insight into local factors prompting vascular disease.